Engineered Living Materials-Based Sensing and Actuation - Liu, Shan; Xu, Weinan (Frontiers in Sensors, 2020)
The integration of functional synthetic materials and living biological entities has emerged as a new and powerful approach to create adaptive and functional structures with unprecedented performance and functionalities, and such hybrid structures are also called engineered living materials (ELMs). ELMs have the potential to realize many highly-desired properties, which are usually only found in biological systems, such as self-powered, self-healing, biosignal-responsive, and self-sustainable. Motivated by that, in recent years, researchers have started to explore the use of ELMs in many areas, among them, sensing and actuation is the area that has the most progress. In this short review, we briefly reviewed the important recent development in ELMs-based sensors and actuators, with a focus on their materials and structural design, new fabrication technologies, and bio-related applications. Current challenges and future directions in this field are also identified to help with future development in this emerging interdisciplinary field.